HealthcareLCA: an open-access living database of health-care environmental impact assessments. Issue 12 (December 2022) - Drew, Jonathan; Christie, Sean D; Rainham, Daniel; Rizan, Chantelle
Summary: Anthropogenic environmental change negatively effects human health and is increasing health-care system demand. Paradoxically, the provision of health care, which itself is a substantial contributor to environmental degradation, is compounding this problem. There is increasing willingness to transition towards sustainable health-care systems globally and ensuring that strategy and action are informed by best available evidence is imperative. In this Personal View, we present an interactive, open-access database designed to support this effort. Functioning as a living repository of environmental impact assessments within health care, the HealthcareLCA database collates 152 studies, predominantly peer-reviewed journal articles, into one centralised and publicly accessible location, providing impact estimates (currently totalling 3671 numerical values) across 1288 health-care products and processes. The database brings together research generated over the past two decades and indicates exponential field growth.